Tamadun Islam dan Penguasaan Ilmu - Sidik @ Mat Sidek, Roziah (Jurnal Usuluddin, 2009)
This article seeks to highlight the excellence of the Islamic civilization from the aspect of mastery of knowledge. In this context, mastery of knowledge includes that of scholars who were vigorously active in the Islamic civilization and the mastery of the knowledge which later made way for the creation and development of the Islamic civilization. This article is based on the methodology of library research. The writer finds that the excellence of the Islamic civilization became prominent through the extensiveness of the knowledge possessed by the scholars of the Islamic civilization. Mastery of knowledge is perceived in the industrious collection of materials and manuscripts which were subsequently translated into the Arabic language. In addition, the writer also finds that the mastery of knowledge in the Islamic civilization bears a relation to the usage of the language which could be understood by every member of the society. Herein lies the role of the Arabic language which was the one and only language used in the daily life of the society in the whole of the Islamic dominion then. The writer also finds proof of mastery of knowledge in the Islamic civilization from the ability to accomplish original works in a given field. These original works are evidence of intellectual brilliance and symbolize the superiority of the scholars’ knowledge.